Multisystem Langerhans Cell Histiocytosis With Braf V600e Mutation In A Child: A Case Report - Valentin. J, Mary; S, Jagadesh.; Dheenadhayalan, M.; . Karthickeyan, K; Shanmugasundaram, P.; SUNDAR SRI, M. K. (Journal of Neonatal Surgery, 2025)
Background: Langerhans Cell Histiocytosis (LCH) is a clonal proliferation disease of Langerhans cells with low incidence affecting one or more organs. Liver involvement, especially BRAF V600E mutation, has an unfavorable prognosis. Case Presentation: We report a case of a 2-year-old boy with worsening cholestatic jaundice, cutaneous lesions, polydipsia, and weight loss. Histopathology revealed multisystem LCH with CD1a positivity and BRAF V600E mutation. PET-CT scan showed hepatic and lymph node disease. The disease worsened despite vinblastine-based chemotherapy. Cytarabine was initiated, followed by dabrafenib as a bridging therapy. The child was formally listed for a liver transplant. There are significant implications for clinical practice. Conclusion: This case highlights the rare multisystem presentation of BRAF-positive LCH with liver failure and the utility of combining mutation-targeted therapy with transplant planning. Given the refractory nature of disease in such genetic subtypes, there is a need for multidisciplinary coordination among oncologists, hepatologists, and transplant surgeons to optimize the timing and outcomes of curative therapies